Optimizing techniques and dynamics in individual sports - Iglesias, X.; Anguera, M. T.; Prieio, I.; Gutierrez, A.; Camerlno, O.; Campanico, J. (Mixed methods research in the movement sciences: Case studies in sport, physical education and dance, 2014)
Case Study 1: The influence or environmental factors in thecontext of elite fencing Case Study 2: Errors in the judo throw Ippon Seoi Nage and their consequences for the learning process Case Study 3: Analysis of specific technical behaviour in freestyle swimming. This three case studies consider ways of optimizing performance in individual sports, specifically, fencing, judo and swimming. Each case study uses observational methodology to develop specific observation and recording instruments which, in combination with other tools, are applied in order to analyse certain parameters: temporal parameters in fencing, biomechanical parameters in judo and physiological parameters in swimming. Individual sports are not subject to the same contextual factors as are team sports, and this affects the technical aspects which coaches need to focus on, doing so on an individualized basis that reflects the particular characteristics of each athlete. In this regard, the first case study shows how factors such as the available space, the lime remaining and the score at any given point may influence the actions of competitors. The second case study, which focuses on judo, highlights the need for coaches to be aware of the basic errors or sequences of errors that combatants may commit when performing a throw, as this can help them plan their teaching strategies. Finally, the third case study shows how an analysis of the aerobic and technical capacity of swimmers can be used to improve their performance in freestyle swimming.